Determination of the Depth of Closed Blind Cracks in Non-metal Check Samples and Test Panels for Penetrant Testing; MATEC Web of Conferences; Vol. 79 : Information-Measuring Equipment and Technologies (IME&T 2016) - Kalinichenko N. P. Nikolay Petrovich; Lobanova I. S. Irina Sergeevna; Zaitseva A. Anna; Loboda E. Egor; Kalinichenko A. N. Aleksey Nikolaevich (2016, 2016)
Title screen